2017
DOI: 10.1111/acem.13247
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Value of Hybrid Single‐photon Emission Computed Tomography With Computed Tomography Imaging in Pulmonary Embolism Diagnosis

Abstract: ObjectiveThe objective was to quantify the potential economic value of single‐photon emission computed tomography (SPECT) with computed tomography (CT; SPECT/CT) versus CT pulmonary angiography (CTPA), ventilation–perfusion (V/Q) planar scintigraphy, and V/Q SPECT imaging modalities for diagnosing suspected pulmonary embolism (PE) patients in an emergency setting.MethodsAn Excel‐based simulation model was developed to compare SPECT/CT versus the alternate scanning technologies from a payer's perspective. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…A French study (584 patients, 2005) stated inconclusive findings in 3% of V/Q SPECT reports . A recent meta‐analysis performed in the United States determined the weighted average of equivocal V/Q SPECT to be 5.8% . However, the standard technique for V/Q SPECT in the US involves the use of Xenon radiotracer rather than Technegas rendering direct comparison of equivocal rates less useful.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A French study (584 patients, 2005) stated inconclusive findings in 3% of V/Q SPECT reports . A recent meta‐analysis performed in the United States determined the weighted average of equivocal V/Q SPECT to be 5.8% . However, the standard technique for V/Q SPECT in the US involves the use of Xenon radiotracer rather than Technegas rendering direct comparison of equivocal rates less useful.…”
Section: Discussionmentioning
confidence: 99%
“…V/Q SPECT is also used as a second line investigation when a CTPA study is non‐diagnostic or has equivocal findings. Recently, a few systematic reviews and meta‐analyses have been published which concluded that V/Q SPECT was superior or equal to CTPA in most clinical settings with better overall diagnostic performance …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Descriptive data from single-modality series were used if direct comparison data were unavailable. Sample size weighted estimates were synthesized in the case of multiple data sources to mitigate outlier bias (45).…”
Section: Model Scaffoldmentioning
confidence: 99%